The Impact of Perceived Usefulness, Perceived Ease of Use, and Digital Literacy on QRIS Adoption - Ikwanto, Azisma Nur Putri; Indriani, Farida (LifeSciFi, 2024)
This study aims to analyze the impact of perceived usefulness, perceived ease of use, and digital literacy on the intention of Micro, Small, and Medium Enterprises (MSMEs) to adopt Quick Response Code Indonesian Standard (QRIS) to support economic digitalization for community development. Using a quantitative approach, this research examines three primary independent variables: perceived usefulness, perceived ease of use, and digital literacy, and their effect on the dependent variable, which is MSMEs' intention to use QRIS (Y). Data were gathered through a survey of 50 MSME owners in Central Java who have implemented QRIS as a digital payment method. Regression analysis results indicate that both perceived usefulness and perceived ease of use have a significant positive influence on the intention to use QRIS. Digital literacy is also found to contribute significantly to MSMEs' interest in using QRIS, especially by enhancing their confidence in technology and reducing technical barriers. The findings suggest that perceived usefulness and ease of use play essential roles in encouraging MSMEs to adopt digital payment technologies. Moreover, higher digital literacy supports MSMEs' readiness to engage in an inclusive digital economy, thereby accelerating community development. These insights provide valuable guidance for policymakers and stakeholders to improve digital infrastructure and literacy, fostering MSME growth through economic digitalization.